Programa LEM: Tocar e Cantar: um lugar de formação e atuação acadêmico profissional - Schwan, Ivan Carlos (2009)
This work is linked to the line of research Education and Arts in the Post Graduation Program in Education, in the Federal University of Santa Maria and the group FAPEM: Training, Action and Research in Music Education. The objective of the present research was to investigate the impact of the Program LEM: Playing and Singing "for the training and teacher development, from the perspective of student teachers in music/workshop organizers. According to this objective, it is intended to know the aims of undergraduate students to participate as workshop participants of the workshops of the program LEM to analyze the relationships established between the music workshops, its training and development staff, understanding the assumptions that underlie the development of education in the workshops and also place the "Program LEM: Play and Sing" in the context of academic and professional training. The qualitative methodological approach was chosen to analyze the perspectives of seven workshop participants as the subjects of the present research. For data collection it was used the semi-structured interview, which took place in two stages: the first session on Individual (EI) and the second group (EG). Thus, data analysis was established by qualitative analysis, performed from the relationship between the perspectives of workshop participants, workshops in music, education and the development of education. From the interpretation of the background and the references about teacher training and professional development, the conception of the process of training student teachers in music workshops in the Laboratory for Music Education was developed, researching this area as a place of training and academic and professional performance. As a result, we present the "LEM Program: Play and Sing" by addressing its significance for the undergraduates, the relationship between the experiences in music workshops and training, and setting out the objectives of the workshop participants to participate in the program according to assumptions that underlie their teaching in music workshops. Still, we highlight the LEM program as a place of training and academic and professional performance.